Q: What is -1 cubed?

Write your answer...

Submit

Related questions

They are cubed values. 1 cubed is 1, 2 cubed is 8, 3 cubed is 27, 4 cubed is 64, 5 cubed is 125 and 6 cubed is 216.

1 cm cubed = 1 cm X 1 cm X 1 cm 1 cm = .01 m, so 1 cm cubed = .01 m X .01 m X .01 m Therefore, 1 cm cubed = .000001 m cubed, and 243 cm cubed = 243 X .000001 = .000243 m cubed. In summary, multiply cm cubed by .000001 to get m cubed.

multiply 0.65 m cubed by 1.15 and you'll get 1 m cubed.

1 cubed = 13 = 1 x 1 x 1 = 1.

No - a millilitre is equal to a centimetre cubed, not a millimetre cubed.

1 cubed = 13 = 1x1x1 = 1 2 cubed = 23 = 2x2x2 = 8 3 cubed = 33 = 3x3x3 = 27 4 cubed = 43 = 4x4x4 = 64 5 cubed = 53 = 5x5x5 = 125

To convert 1 mm cubed to 1 m cubed simply remember that you also have to cube your conversion factor. This means that your equation is 1 mm^3(1 m/10^3 mm)^3. 1 mm cubed = 1.0 x 10^-9 m cubed.

1 metre cubed is 100 cm cubed so 1,000,000

1 centimeters cubed = 1000 millimeters cubed

one billion because 1000 m = 1 km so there are 10003 = 1 billion meters cubed in a kilometer cubed.

1 cubed foot = 28.32 litres (approx).

A meter is 1000 millimeters so 1 meter cubed is 1,000,000mm cubed.

1 decimetre (dm) = 10 centimetre (cm) so 1 dm cubed = 10 cm cubed = 10 cm * 10 cm *10 cm = 1000 cm cubed

0.1

.001m's

Well, 1 cubed is 1*1*1 Therefore, 1 cubed would equal 1

Yes. 1 to the power of 3 is still one, so 1 is a cubed number.

The integral of cosine cubed is sinx- 1/3 sin cubed x + c

Because 1 cubed , 5 cubed , 3 cubed added together make 153

1 cm cubed = 0.001 litre.

1 metre cubed = 100 cm * 100 cm * 100 cm = 1 000 000 cm cubedso 125 000 cm cubed in metres cubed = 125 000 / 1 000 000 = 0.125 m ^3

1 Dm(cubed) 1000 Cm (cubed) 1000 ml

1

-1

xcubed-1 Answer::(X-1)(Xsquared+X+1) when you factor xcubed minus a number its the same thing as x cubed minus y cubed and x cubed minus y cubed factors to:: (x-y)(xsquared+xy+y squared) the first factor, (x-y), is the cubed root of the first and the cubed root of the second, so in the answer i have (x-1), which is x cubed minus one cubed :) the second factor, (xsquared+xy+ysquared), you take the first number squared, Xsquared, then the first and second one multiplied together, XY, and then the second number squared, Ysquared, so in the answer i have (xsquared+x+1), which is x squared, then x times 1 which is just x, and positive 1, which is negative 1 squared :) x^3 - 1

Study guides